If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -5y + 9 = -6y + 2 Reorder the terms: 9 + -5y = -6y + 2 Reorder the terms: 9 + -5y = 2 + -6y Solving 9 + -5y = 2 + -6y Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '6y' to each side of the equation. 9 + -5y + 6y = 2 + -6y + 6y Combine like terms: -5y + 6y = 1y 9 + 1y = 2 + -6y + 6y Combine like terms: -6y + 6y = 0 9 + 1y = 2 + 0 9 + 1y = 2 Add '-9' to each side of the equation. 9 + -9 + 1y = 2 + -9 Combine like terms: 9 + -9 = 0 0 + 1y = 2 + -9 1y = 2 + -9 Combine like terms: 2 + -9 = -7 1y = -7 Divide each side by '1'. y = -7 Simplifying y = -7
| z-49=-19 | | (4+3)+(x-8)=90 | | 2.4s=-4.8 | | -8+7n=8n-7 | | 5(y+5)=6(y-5) | | -v=6+3 | | 1-x=14 | | 3(n-2)+4(n+3)+2(n+4)=140 | | -5+6m=7m+9 | | -v=-3+6 | | 2(x-7)=4(2x+3) | | y=x^2-6table | | 5(5x-8)-3(-1-8x)=35+50x | | r-6=-7 | | 5v+8=4v | | 7x+10+3x=180 | | u-2=-6 | | 4-2=-6 | | 8x-4=7x | | w-9=3 | | 3w+5=2w | | x-3=-9 | | 7n+6=8n | | u-4=8 | | 4+2=-6 | | x(9x-5)=45 | | 8(t-4)+4t=4(3t+3)-10 | | 4n+7=5n | | -7a+2+8a=12-29 | | ((9a+3b+44c)*2)=b | | (((13+x)*2-44)*9)=X | | (((x*4)-12*4)*2)=x |